2017
DOI: 10.1111/pedi.12561
|View full text |Cite
|
Sign up to set email alerts
|

Serum and gene expression levels of CT-1, IL-6, and TNF-α after a lifestyle intervention in obese children

Abstract: We reported that serum CRP, TNF-α, as well as PBMC CT-1 transcript levels were reduced after lifestyle intervention in obese children. More studies are needed to clarify the role of inflammation-related molecules in glucose metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…Our results show that those children who had a late dinner had 1.4-fold CRP and 1.6-fold IL-6 values than early eaters. These two pro-inflammatory biomarkers have been related to BMI and have been involved in the pathogenesis of obesity [34,35], which suggests a deleterious association of late eating with inflammatory markers at these ages. Interleukine-6 (IL-6) is the main regulator of the acute inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that those children who had a late dinner had 1.4-fold CRP and 1.6-fold IL-6 values than early eaters. These two pro-inflammatory biomarkers have been related to BMI and have been involved in the pathogenesis of obesity [34,35], which suggests a deleterious association of late eating with inflammatory markers at these ages. Interleukine-6 (IL-6) is the main regulator of the acute inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…After 4 weeks, blood samples were collected via ocular sampling for isolated serum by clot 2 h at the room temperature and were then centrifuged at 1100 × g for 15 min as previously described. [26] Then liver tissue and colon content were collected and transferred to liquid nitrogen. Serum was collected to analyze LPS, blood glucose, TC, TG, high-density lipoprotein cholesterol (HDL-c), LDL-c, pancreas tissue for gene expression of phosphoinosmde-3-kinase (PI3K), protein kinase B (Akt), IL-2, IL-6, TNF-α, TGF-β, and contents of colon for gut microbiota.…”
Section: Sample Collection and Measurementmentioning
confidence: 99%
“…Also, they observed a positive association between CT-1 and arterial damage (increase intima-media thickness). In addition, in obese children, CT-1 transcript levels were reduced after lifestyle interference [80]. Furthermore, Anik Ilhan et al [81] demonstrated that CT-1 levels were found to be positively correlated with DBP and triglyceride levels in MS women with polycystic ovaries.…”
Section: Discussionmentioning
confidence: 99%